Biopharmaceutical Assessment of Mesh Aerosolised Plasminogen, a Step towards ARDS Treatment - Lucia Vizzoni; Chiara Migone; Brunella Grassiri; Ylenia Zambito; Baldassare Ferro; Paolo Roncucci; Filippo Mori; Alfonso Salvatore; Ester Ascione; Roberto Crea; Semih Esin; Giovanna Batoni; et al. (MDPI AG, 2023)
Acute respiratory distress syndrome (ARDS) is a severe complication of lung injuries, commonly associated with bacterial, fungal and viral infections, including SARS-CoV-2 viral infections. ARDS is strongly correlated with patient mortality and its clinical management is very complex, with no effective treatment presently available. ARDS involves severe respiratory failure, fibrin deposition in both airways and lung parenchyma, with the development of an obstructing hyaline membrane drastically limiting gas exchange. Moreover, hypercoagulation is related to deep lung inflammation, and a pharmacological action toward both aspects is expected to be beneficial. Plasminogen (PLG) is a main component of the fibrinolytic system playing key roles in various inflammation regulatory processes. The inhalation of PLG has been proposed in the form of the off-label administration of an eyedrop solution, namely, a plasminogen-based orphan medicinal product (PLG-OMP), by means of jet nebulisation. Being a protein, PLG is susceptible to partial inactivation under jet nebulisation. The aim of the present work is to demonstrate the efficacy of the mesh nebulisation of PLG-OMP in an in vitro simulation of clinical off-label administration, considering both the enzymatic and immunomodulating activities of PLG. Biopharmaceutical aspects are also investigated to corroborate the feasibility of PLG-OMP administration by inhalation. The nebulisation of the solution was performed using an Aerogen® SoloTM vibrating-mesh nebuliser. Aerosolised PLG showed an optimal in vitro deposition profile, with 90% of the active ingredient impacting the lower portions of a glass impinger. The nebulised PLG remained in its monomeric form, with no alteration of glycoform composition and 94% of enzymatic activity maintenance. Activity loss was observed only when PLG-OMP nebulisation was performed under simulated clinical oxygen administration. In vitro investigations evidenced good penetration of aerosolised PLG through artificial airway mucus, as well as poor permeation across an Air-Liquid Interface model of pulmonary epithelium. The results suggest a good safety profile of inhalable PLG, excluding high systemic absorption but with good mucus diffusion. Most importantly, the aerosolised PLG was capable of reversing the effects of an LPS-activated macrophage RAW 264.7 cell line, demonstrating the immunomodulating activity of PLG in an already induced inflammatory state. All physical, biochemical and biopharmaceutical assessments of mesh aerosolised PLG-OMP provided evidence for its potential off-label administration as a treatment for ARDS patients.